Born to Run: The Transmedia Evolution of the Bruce Springsteen Memoir from Book to Stage and Screen. Issue 3 (27th May 2022) - Watson, Laura
ABSTRACT: This article explores how the genre of rock memoir took a new cultural and commercial turn with the publication of Springsteen's book Born to Run (2016). It traces how the book became the foundation for a transmedia project that unfolded across several platforms (including the Broadway stage and Netflix) over the course of two years (2016–2018). This transmedia project worked to construct the twenty-first-century Springsteen as an artist and commentator whose work lies at the intersections of rock, popular literature, scripted theater, and the screen.